Blended Finance: Konsep & Penerapan di Indonesia - Derry Wanta; Arina Felita; Rinto Noviantoro (UNIVED Press, 2022)
This study aims to find out what and how Blended Finance is and specifically and to provide new insights and practical examples of Blended Finance in Indonesia. This research is qualitative research with a library study approach and interviews with practices in the field of Blended Finance. This research reveals a new definition of Blended Blended Finance as one of the systems that can answer the need for funds to make the SDGs a success by using the 4P funds, namely public, private, philanthropy and people. Blended Finance in Practice in Indonesia, among others, SDG Indonesia One, Tri Hita Karana Roadmap Blended Finance, The Sustainability Project Bond from the Tropical Landscape Finance Facility (TLFF), and the Marine and Fisheries Funding Institution (IPKP). The challenges in implementing Blended Finance in Indonesia are building a general knowledge base, lack of coordination or the emergence of ego institutions and the absence of appropriate projects or programs that are ready for financing. The existence of personnel or institutions as a tailoring project is the key to the success of blended finance.